Knowledge and smart sensing for an accessible city. Experimenting on the territory of Friuli Venezia Giulia - Mickeal Milocco Borlini; Christina Conti (Agathón)
The contribution presents state-of-the-art critically through the results of some applied research financed with public funds in areas related to the concept of innovability understood as an ‘innovative’ approach to the environmental accessibility of urban places. This condition is functional to planning, implementing, and managing urban contexts from an environmental and economically ‘sustainable’ point of view. Through these experiences, it is possible to give a sufficiently an in-depth picture of the ICT tools adopted, and the potential of the tools and experiences created. Focusing on users’ needs and evaluating urban/environmental performance leads to evaluating the current situation in medium-sized urban centres. The reported case studies show the high potential of computerisation of the urban management processes, which does not correspond to a convincing social, economic, political and cultural context due to its partial and inefficient application of ICT. These results present some possible actions on the interface and governance of the human-built environment to design a future ‘smart’, ‘innovative’ and ‘sustainable’ city.